West Bank and Gaza Strip : economic developments in the five years since Oslo - Alonso-Gamo, Patricia; Alier, M.; Baunsgaard, Thomas .; Von Allmen, Ulric Erickson; International Monetary Fund. (Washington, D.C. : Middle Eastern Department, International Monetary Fund, 1999)
This paper assesses macroeconomic developments and progress in institution building during 1994-1998. The five year interim period envisaged in the peace accords has ended, and the paper takes stock of what happened in this period. The paper was prepared in the Spring of 1999 and draws on work done by IMF staff visits to West Bank and Gaza in the fall of 1998 and Spring of 1999. It analyzes developments in a number of areas and draws lessons for the future.
Includes bibliographical references: p. 85-86.
rpm 26/09/2016
Ref
Keywords: Banks and banking; Infrastructure (Economics).; Fiscal policy; West Bank; Gaza Strip